Study of rock displacement with the help of equivalent materials using room-and-pillar mining method - Buzilo, V.I.; Savelieva, T.S.; Saveliev, V.A. (London : Taylor & Francis Group, 2012)
Field study made with the help of equivalent materials to determine minimum dimension of interchamber and barrier pillars and limiting chamber span was carried out. Modeling was made for gypsum quarry.
Keywords: room-and-pillar mining; gypsum quarry